Essentials of Pediatric Emergency Medicine Fellowship: Part 4. Issue 8 (August 2016) - Wolff, Margaret; Carney, Michele; Eldridge, Charles; Zaveri, Pavan; Kou, Maybelle
Abstract : Abstract: This article is the third in a 7-part series that aims to comprehensively describe the current state and future directions of pediatric emergency medicine fellowship training from the essential requirements to considerations for successfully administering and managing a program to the careers that may be anticipated upon program completion. This article focuses on the skills beyond clinical training required of pediatric emergency medicine physicians including teaching, leadership, teamwork, and communication.